Study on the Influence of Roadways on Land Plots according to the Results of Monetary Evaluation - Shulgan, Roman; Yanchuk, Oleksandr; Pakharenko, Olha; Pryshchepa, Alla (Geomatics and Environmental Engineering, 2021)
The paper examines the impact of highways of urban significance on surrounding areas. The authors substantiated the size of the road‑effect zone. In order to determine the quantitative extent of the impact of highways on surrounding areas, the scholars applied the data regarding the selling prices of land plots with various designated purpose, i.e. the estimated money value of land is the indicator of determining the road‑effect on surrounding areas. Since a great number of factors affects the value of these land plots, in order to determine the road‑effect for highways, the authors developed economic and statistical models for expert value of land plots with various designated purpose using the method of multiple regression analysis. After substituting different values of distances to a highway within the road‑effect zone in the model, the researchers established the patterns of change in the value of land plots with various designated purpose and calculated the adjustment factors that can be used in the pecuniary valuation of land plots. The value of such coefficients for residential construction land is 0.85‑1.00; for commercial land it is 1.00‑1.17; and for industrial land it is 1.00‑1.01.